Competence profiles in undergraduate dental education: a comparison between theory and reality - Sebastiaan Koole; Shani Van Den Brulle; Véronique Christiaens; Wolfgang Jacquet; Jan Cosyn; Hugo De Bruyn (BMC, 2017)
Abstract Background Competence profiles are purposed to provide a blueprint in support to develop and/or benchmark the learning outcomes of undergraduate dental curricula. This study aims to investigate whether a competence profile as proposed by academic- and clinical experts is able to represent the real clinical reality. Methods A questionnaire was developed including questions about gender and age, perception about required competences, and educational organisation and was distributed among Flemish dentists via email and on paper during a symposium. The data was analysed using descriptive statistics, Chi-square and non-parametric Mann-Whitney U-tests. Results A total of 312 questionnaires were completed (=6.5% of dentist population, with similar gender and age characteristics). All competences in the European competence profile were rated between 7.2 and 9.4 on a 10-point scale. In dentists under 50 years, females rated the importance of identifying/managing anxiety and abnormal patient behaviour; and promoting/improving oral health as significantly higher than males. In dentists of 50 years and above, females rated 8 competences significantly higher than males, including obtaining/recording a complete history; identifying/managing anxiety and abnormal patient behaviour; obtaining/interpreting radiography; identifying temporomandibular and associated disorders; identifying orthodontic needs; awareness of own limitations/when to refer; managing dental urgencies; and basic-life-support/defibrillation. Clinical practice management was most frequently reported as additional competence to address in dental education. Furthermore, the respondents suggested an undergraduate dental curriculum based on 34% theoretical education, 26% preclinical skills training, and 40% clinical education and 86% agreed with a duration of 5 years. Finally, the respondents also illustrated the dynamic nature of dentistry including a reduction of amalgam fillings, a shift from individual practice to group practices, an increased administrative load, and more assertive patients. Conclusion Findings in the present study suggest the validation of the proposed competences for graduating European dentists within the clinical reality of dental professionals in daily practice. Nevertheless, the results have also demonstrated heterogeneity regarding gender and age within the dentist population and emphasised a continuously evolving dental profession and required competences. Hence, to maintain high quality of dental care, a strategy should be developed in which dental curricula are continuously benchmarked against an evolving clinical reality.